Bulk and Active Sediment Prokaryotic Communities in the Mariana and Mussau Trenches - Liu, Rulong; Wang, Zixuan; Wang, Li; Li, Zhenzhen; Fang, Jiasong; Wei, Xing; Wei, Wenxia; Cao, Junwei; Wei, Yuli; Xie, Zhe (Frontiers in Microbiology, 2020)
Surprisingly high rates of microbial respiration have recently been reported in hadal trench sediment, yet the potentially active microorganisms and specific microbe-microbe relationships in trench sediment are largely unknown. We investigated the bulk, active prokaryotic communities and co-occurrence interactions of different lineages in vertically sectioned sediment cores taken from the deepest points of the Mariana and Mussau Trenches. Analysis on species novelty revealed for the first time the high rate of novel lineages in the microbial communities of the hadal trenches. Using 95%, 97% and 99% similarity as thresholds, averagely 22.29%, 32.3% and 64.1% of total OTUs retrieved from sediments of the two trenches were identified as the potentially novel lineages, respectively. The compositions of the potentially active communities, reveled via ribosomal RNA (rRNA), were significantly different from those of bulk communities (rDNA) in all samples from both trenches. The dominant taxa in bulk communities generally accounted for low proportions in the rRNA libraries, signifying that the abundance was not necessarily related to community functions in the hadal sediments. The potentially active communities showed high diversity and composed primarily of heterotrophic lineages, supporting their potential contributions in organic carbon consumption. Network analysis revealed high modularity and non-random co-occurrence of phylogenetically unrelated taxa, indicating highly specified micro-niches and close microbial interactions in the hadal sediments tested. Combined analysis of activity potentials and network keystones scores revealed significance of phyla Chloroflexi and Gemmatimonadetes, as well as several potentially alkane-degrading taxa in maintaining microbial interactions and functions of the trench communities. Overall, our results demonstrate that the hadal trenches harbor diverse, closely interacting and active microorganisms, despite the extreme environmental conditions.